Hubungan Pengetahuan WUS Tentang Kebersihan Area Genital Dengan Kejadian Keputihan di Wilayah Kerja Puskesmas Kecamatan Manisrenggo Klaten - Hernandia Happy Safitri; Wiwin Lismidianti; Ika Hermawati C. (Journal of Health (JoH), 2014)
Background: Leucorrhoea is a disease of the reproductive system that suffered by many women most of the world. One of the causes leucorrhea is a lack of knowledge keep cleaning the genital area. Many factors affecting by the lack of knowledge, one of which is the lack of information. Data on the public health center Manirenggo Klatenin 2013, 153 women of reproductive age on Ngemplak Seneng Village District of Klaten Manis renggo most experience vaginal discharge. Aim: The aim of this research is to know the correlation between knowledge about hygiene the genital area WUS with leucorrhoea, to find out knowledge about hygiene WUS genital area, to find out how much the incidence of leucorrhoea in public health center district Manisrenggo Klaten. Method: This was on non experimental research with also correlation descriptive research that using The cross-sectional design. This research uses purposive sampling with 60 respondents. Analyzed using univariate, bivariate analysis with the Chi-Square test and contingency coefficient test. The research was conducted in public health center district Manisrenggo, Klaten, Central Java, in April until May 2014. Result: Percentage Women of Reproductive Age which has a high knowledge is (56.7%) or about 34 respondents. 26 respondents had low knowledge and 7 (11.7%) of them experienced a leucorrhoea. Parametric test contingency correlation coefficient to determine the relationship of knowledge Women of Reproductive Age about hygiene the genital area with a leucorrhoea incident obtained p-value 0.001. Having interpreted C=0,384 shows a fairly close relationship. Conclusion: There was correlation between knowledge Women of Reproductive Age about hygiene the genital area with a leucorrhea incident. Knowledge of Women of Reproductive Age about hygiene the genital area is in the high category a number of 34 with a percentage of 56.7%, and the incidence of leucorrhoea in public helath center district Manisrenggo Klaten a number of 7 with a percentage of 11.7%.